Clinical significance of epithelial-mesenchymal transition - Steinestel, Konrad (Springer, 2014)
The concept of epithelial-mesenchymal transition (EMT), a process where cells change their epithelial towards a mesenchymal phenotype, has gained overwhelming attention especially in the cancer research community. Thousands of scientific reports investigated changes in gene, mRNA and protein expression compatible with EMT and their possible correlation with tumor invasion, metastatic spread or patient prognosis; however, up to now, a proof of clinical significance of the concept is still missing. This review, with a main focus on the role of EMT in tumors, will summarize the basic molecular events underlying EMT including the signaling pathways capable of its induction as well as changes in EMT-associated protein expression and will very briefly touch the role of microRNAs in EMT. We then outline protein markers that are used most frequently for the assessment of EMT in research and diagnostic evaluation of tumor specimens and depict the link between EMT, a cancer stem cell (CSC) phenotype and resistance to conventional antineoplastic therapies. Furthermore, we evaluate a possible correlation between EMT marker expression and patient prognosis as well as current therapeutic concepts targeting the EMT process to slow down or prevent metastatic spread of malignant tumors.